Evaluation of Three Prokaryote Primers for Identification of Prokaryote Community Structure and Their Abode Preference in Three Distinct Wetland Ecosystems - Kumari, Kavita; Naskar, Malay; Aftabuddin, Md.; Das Sarkar, Soma; Ghosh, Bandana Das; Sarkar, Uttam Kumar; Nag, Subir Kumar; Jana, Chayna; Das, Basanta Kumar (Frontiers in Microbiology, 2021)
The ultimate role of prokaryote (bacteria and archaea) as the decomposer of the ecosystem, easily interrelates its community structure with the surrounding environment. In the present study, we compared prokaryote community structure and identified their abode preference as an indicator of wetland ecosystem in three distict wetland ecosystem using three universal prokaryote primers for the firdt time. Our results showed that Alpha diversity indices and phylogenetic differential abundance pattern did not differ significantly with primers, however those were significantly different across wetlands. Microbial community composition revealed distinct pattern in each wetland with each primer. Overall comparison of bacterial communities in three different wetland sediment revealed highest bacterial richness and diversity in Bhomra (freshwater wetland) followed by Malencho (brackish water bheri) and EKW (sewage-fed wetland). Indicator genus analysis identified 21, 4, and 29 unique genera as the diagnostic genus having abode preference for Bhomra, EKW and Malencho, respectively. Prediction of potential roles of these microbes based on close OTU similarity revealed more abode preference of sulphate reducing microbes in Malencho and methanogens in Bhomra. Distinct phylogenetic differential abundance pattern alongwith microbial abode preference and their potential functional role predicts ecosystem variables shapes microbial diversity. The variation in community composition of prokaryotes in response to ecosystem variables, can serve as the most sensitive bioindicator of ecosystem assessment and management.